PARTICIPATION AND PRODUCTION : A BRIEF NOTE ON THE PHILOSOPHICAL APPROACH TO ART - Khataniar , Ansuman (International Journal of Psychosocial Rehabilitation, 2020)
The human mind is deeply engaged with the world around it. The cognitive and the contemplative are two related dimensions of this engagement. But there is another relationship in which man is not just a passive onlooker. Here he is a participant who seeks to create. This participation may be technical participation in which the main motive is domination over nature. In another form of participation the creative and aesthetic senses are domination and here man seeks to bring forth or elicit beauty. Human aesthetic sensibility has an apriori foundation and philosophers like Kant seek to analyse that apriori foundation. In art, as Heidegger pointed out, we find a creative preservation of truth. The truth that we find in art is not mere propositional truth. It is a truth connected with the revelation of a whole world and in a distinctive sense in a work of art truth establishes itself. Many works of art definitely contain moral messages as well. In Indian philosophy the aesthetic sensibility is connected with ‘ananda’ and this ‘ananda’ with its cosmic dimension has a moral implication as well.